Cultural Interference in Indonesian Folktale Writing in Japanese - Puspitosari, Dwi; Setiawati, Ai Sumirah; Rochim, Julita Fahrul; Kaede, Toguchi; Ananto, Tohru Tanaya Paramudya (IJLHE: International Journal of Language, Humanities, and Education, 2026)
This study examines cultural interference in Indonesian folktale writing in Japanese produced by university-level learners of Japanese as a foreign language. The research aims to identify patterns of cultural interference and to describe how Indonesian cultural concepts are transferred, adapted, or inadequately represented in Japanese narrative texts. Employing a qualitative descriptive approach, the study analyzes 39 folktales written by Indonesian students at intermediate to upper-intermediate proficiency levels. The data were analyzed at lexical, grammatical, and discourse levels using contrastive analysis, error analysis, interlanguage analysis, and contrastive rhetoric. The findings reveal that cultural interference occurs consistently across all texts. Lexical interference is reflected in inappropriate word choice and the use of culturally bound terms without adequate adaptation. Grammatical interference appears in inconsistent sentence-final forms, inaccurate tense and aspect marking, and frequent misuse or omission of particles. At the discourse level, interference manifests through abrupt subject shifts, non-natural sentence structures, and insufficient contextual introduction of characters and settings, which disrupt narrative coherence. The study demonstrates that cultural interference in foreign language writing extends beyond linguistic error and represents learners’ ongoing intercultural negotiation. The findings highlight the importance of integrating cultural discourse awareness into Japanese language writing instruction, particularly in narrative-based learning contexts.